How to Put the Cart Behind the Horse in the Cultural Evolution of Gender. Issue 1 (January 2022) - Saunders, Daniel
In The Origins of Unfairness, Cailin O'Connor develops a series of evolutionary game models to show that gender might have emerged to solve coordination problems in the division of labor. One assumption of those models is that agents engage in gendered social learning. This assumption puts the explanatory cart before the horse. How did early humans have a well-developed system of gendered social learning before the gendered division of labor? This paper develops a pair of models that show it is possible for the gendered division of labor to arise on more minimal assumptions.